Electrocardiography on admission is associated with poor outcomes in coronavirus disease 2019 (COVID-19) patients: A systematic review and meta-analysis - Mochamad Yusuf Alsagaff, - (Wiley-Blackwell, 2021)
Background Electrocardiogram (ECG) is a widely accessible diagnostic tool that can easily be obtained on admission and can reduce excessive contact with coronavirus disease 2019 (COVID-19) patients. A systematic review and meta-analysis were performed to evaluate the latest evidence on the association of ECG on admission and the poor outcomes in COVID-19.